Analysis of volatile compounds between raw and cooked beef by HS‐SPME–GC–MS. Issue 2 (17th October 2017) - Wang, Xiaodan; Zhu, Lingtao; Han, Yunxiu; Xu, Liping; Jin, Jiahui; Cai, Yingming; Wang, Hongmei
Abstract: Volatile flavor compounds of three raw and cooked beef cuts (rib, flank, and shank) were analyzed by HS‐SPME–GC–MS. Based on the specificity of volatile substances in beef, an orthogonal test for HS‐SPME was designed and the extraction temperature, extraction time and desorption time were studied and optimized. The appropriate conditions for beef volatiles detection were: a 2 min desorption and a 50 min extraction at 80 °C. A total of 61 volatiles were detected successfully. Variety of volatiles was nearly consistent while contents were slightly different among three parts. Meanwhile, in the same part, types and contents of volatiles were different between raw and cooked beef, which could explain why the raw beef are basically not fragrant and flavors were generated after cooked. The optimization of HS‐SPME–GC–MS provided valuable information of beef ingredients, and the aroma changes can also reflect the change of beef taste. Practical applications: Beef volatile compounds between raw and cooked, which can be a prime exploration of beef quality and taste trait in the field of food flavor, that how the special beef aromas change between raw and cooked beef was studied and the source of some certain chemical substances were traced to explain for the special beef flavor. Besides, this article can be a preliminary study to analysis beef flavor by sensor detection. The sample was prepared into a liquid state and could be well applied in electrochemical detection. In view of the development of rapid detection techniques, sensory evaluation is popular but lack of objectivity and repeatability. It is intended to contrive a new sensor array or biosensors to analyze the beef taste quality during the processing. The measurement can be a mature verification to sensor detection and can be applied to other meat products.